2014
DOI: 10.1002/pbc.25098
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function abnormalities in childhood cancer survivors treated with bleomycin

Abstract: More than half the patients who received bleomycin had subclinical pulmonary dysfunction as evidenced by abnormalities in pulmonary function tests, although the incidence of clinical symptoms was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 48 publications
3
36
0
1
Order By: Relevance
“…Moreover, bleomycin is known to induce a wide variety of respiratory and pulmonary dysfunctions, including pulmonary fibrosis. 32 Systemic toxicity is low in ECT because the bleomycin doses administered systemically are relatively low (the very high intratumoral concentrations of cytostatic agents are a result of electroporation). Nevertheless, 1 patient in our study died from a worsening of underlying pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bleomycin is known to induce a wide variety of respiratory and pulmonary dysfunctions, including pulmonary fibrosis. 32 Systemic toxicity is low in ECT because the bleomycin doses administered systemically are relatively low (the very high intratumoral concentrations of cytostatic agents are a result of electroporation). Nevertheless, 1 patient in our study died from a worsening of underlying pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…34 Among AYA survivors of childhood cancer who had received bleomycin, De et al found at least one pulmonary function abnormality, including obstructive lung disease, and impairments in lung capacity, expiratory volume, expiratory flow, and residual volume, in 52.5% of survivors after a median follow-up time of 3.9 years after diagnosis. 35 Similarly, after a median of 18 years of follow-up among childhood cancer survivors treated with bleomycin, Mulder et al found pulmonary function impairments in 44% of survivors. 36 37 Finally, using a comprehensive systematic clinical assessment, Hudson et al found that the prevalence of adverse outcomes by organ system among adult survivors of childhood cancer was highest for the pulmonary system, with abnormal pulmonary function found in 65.2% of survivors after a median time from diagnosis of 25 years.…”
Section: Pulmonary Limitationsmentioning
confidence: 97%
“…Treatment for HL typically includes a vinca-alkaloid agent, which can affect peripheral nervous system function (10). A prospective study should also include measures of cardiac perfusion, myocardial contractility, and pulmonary function to determine if autonomic dysfunction is an impairment that can be distinguished from ischemia, myopathy, valve disease, and pulmonary abnormalities and so that contributions of these known problems among HL survivors to ETT can be accounted for (11)(12)(13)(14).…”
mentioning
confidence: 99%